Sustainability Efforts in Eco-Fashion Industry: Consumer Perception Trust and Purchase Intention - Ramadina, Tarisya Rizki ; Pradana, Mahir; Rubiyanti, Rd. Nurafni (Asian Journal of Management Analytics, 2025)
The sustainable fashion industry is experiencing rapid growth as consumer awareness of environmental issues increases. This study aims to analyze the influence of Social Responsibility on Purchase intention in sustainable fashion products, with Trust, Attitude, and Perceived Consumer Effectiveness (PCE) as the mediating variables. The object of the research is consumers of Eiger eco-fashion products in Indonesia. The method used is explanatory quantitative with an online survey approach and Partial Least Square (PLS-SEM) analysis techniques. The sample amounted to 200 respondents who were selected using purposive sampling. The results of the study show that Social Responsibility has a positive effect on Trust, Attitude, and PCE. In addition, Trust and Attitude have a significant effect on Purchase intention, while PCE also makes a positive contribution. This research provides practical implications for companies in strengthening sustainability strategies to increase consumer buying intentions, while enriching the academic literature on sustainable consumer behavior in Indonesia.